2007
DOI: 10.1139/l06-150
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of binder and mix properties to detect reclaimed asphalt pavement content in bituminous mixtures

Abstract: The purpose of this study was to recommend a testing procedure to detect the content of reclaimed asphalt pavement (RAP) used in hot-mix asphalt mixtures. Asphalt was extracted from RAP for use in blending with new binder and aggregate. The recovered binders were blended with virgin asphalt (AC-10) at 10 different concentrations. A concept called relative energy loss was proposed to determine the engineering properties of recycled asphalt concrete (RAC). The relative energy loss was found to be directly relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…The prism trabecula with a height of 30 mm ± 0.5 mm and a height of 35 mm ± 0.5 mm has a span of 200 mm ± 0.5 mm. 3 Use the MTS testing machine (MTS-810, MTS Systems Corporation, Minneapolis, MN, USA) for loading at a loading rate of 500 mm/min. 4 Put the cut specimens into an environmental incubator for heat preservation and curing at 15 • C for more than 4 h and, finally, conduct an impact toughness test, as shown in Figure 13.…”
Section: The Influence Of Different Processed Aggregates On the Perfo...mentioning
confidence: 99%
See 2 more Smart Citations
“…The prism trabecula with a height of 30 mm ± 0.5 mm and a height of 35 mm ± 0.5 mm has a span of 200 mm ± 0.5 mm. 3 Use the MTS testing machine (MTS-810, MTS Systems Corporation, Minneapolis, MN, USA) for loading at a loading rate of 500 mm/min. 4 Put the cut specimens into an environmental incubator for heat preservation and curing at 15 • C for more than 4 h and, finally, conduct an impact toughness test, as shown in Figure 13.…”
Section: The Influence Of Different Processed Aggregates On the Perfo...mentioning
confidence: 99%
“…However, they do not pay enough attention to the processing characteristics, such as the content of needle and flake particles of stone, the proportion of broken surface of broken gravel, mud content, angularity, grading composition, and the roughness and angularity of machine-made sand [2]. Previous studies have shown that the size, shape, gradation and morphology of aggregate have a significant impact on the road performance of asphalt mixture, which is directly related to the deformation characteristics and fatigue resistance of asphalt mixture [3]. In order to be able to design a long-life asphalt pavement, the aggregate must have reasonable morphology and morphological characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En Estados Unidos, la National Asphalt Pavement Association (NAPA) afirma que las mezclas que contienen altos porcentajes de RAP (30-40 %) se pueden producir, aunque la restricción para su fabricación radica en que la rigidez aumenta a mayor contenido de RAP (Newcomb, Brown y Epps, 2007). Otros investigadores encontraron que el 40 % de RAP, es el contenido máximo permitido para resistir deformaciones permanentes y agrietamientos por fatiga (Chen, Chu y Lin, 2007).…”
Section: Introductionunclassified
“…There are abundant data indicating that properly specified and produced recycled hot mix asphalt is equivalent to conventional hot asphalt in terms of rutting, raveling, weathering and fatigue cracking (Solaimania et al, 1996;Stroup-Gardiner et al, 1999;Soleymani et al, 2000;Karsson et al, 2003;Buttlar et al, 2005;Airey et al, 2005;Chen et al, 2007;Miro et al, 2008;Daniel et al, 2008). Apparently the paving industry has started the use of R 2 AP in binder and surfaces courses.…”
Section: Introductionmentioning
confidence: 99%